Congestible Goods and Hoarding: A Test based on Students' Use of University Computers - Martijn B.W. Kobus; Jos N. van Ommeren; Hans R.A. Koster; Piet Rietveld (Tinbergen Institute, 2013)
For certain goods, higher levels of congestion imply higher levels of expected future entry costs. This provides current users of the good with an incentive to hoard, that is, to lengthen their duration of good use, in order avoid entry costs later on. We test for hoarding of university computers by students. Endogeneity of congestion is acknowledged by using an instrumental variable approach. Our results indicate that congestion has a strong effect on hoarding behaviour. More specifically, it is shown that the congestion elasticity of computer duration is about 0.57.
Keywords: D00; 330; congestible goods; hoarding; computer use